Korean Cultural Communication Seminar: The ‘Oppa’ and ‘Unnie’ Influence in Contemporary Tea Marketing - Syifa Fatimazzahroh; Indrati Asyariri Fatimazzahroh; Adhitya M. Maheswara Fatimazzahroh; Lia Amelia Nurkhazanah Fatimazzahroh (Universitas AMIKOM Yogyakarta, 2026)
This community service initiative is driven by the pervasive influence of the Korean Wave, which presents creative marketing opportunities for tea products in Tarumajaya Village. The objective is to enhance MSME capacity through a Korean cultural communication approach. The methodology includes situational analysis, implementation of seminars and branding workshops, and final evaluation. Participants comprise local tea-producing MSMEs. Results indicate a significant transformation; prior to the program, branding was conventional with limited social media engagement. Following the intervention, participants demonstrated the ability to integrate Korean vocabulary and visual elements into product labels and slogans. Success indicators showed a 75% improvement in creative marketing communication skills based on practical evaluation results. In conclusion, the SEKOMBUDKOR program provides significant added value to local product branding, resulting in stronger visual appeal and broader market potential among the younger generation.